"Vergil and Homer opened my Books:" The Sibylline Oracles and the non-Jewish canon. (December 2022) - Van Noorden, Helen
The hybrid cultural weave of the Sibylline Oracles is one of the most arresting aspects of a collection which preserves Judaeo-Christian compositions in Greek ranging from c . second century BCE to the seventh century CE. Reviewing world history in the form of prophecy, sketching rewards and punishments due at the end of days, and urging ethical behavior, these oracles in Homerizing hexameters combine Classical and Biblical traditions and are attributed to an ancient Sibyl. This article focuses on a distinctive case of repetition within the Sibylline corpus to highlight how the sense of a Classical canon is updated in the Jewish development of this prophetic genre. The passages triggering both intertextual and intratextual investigation ar Sibylline Oracles 3.419–25, which "predicts" that the blind Homer will be the first to open the Sibylline books and copy her tale of Troy, and the far less studied Sibylline Oracles 11.163–71, where phrases about Homer are revised to produce an emphasis on Vergil's skill as a poet and discretion in concealing the Sibylline writings until his death. Study of these lines in their immediate and wider narrative contexts reveals the Jewish sibyllists exploiting the literary knowledge of Classically-educated readers, first and foremost in order to build up the Sibylline authority, a priority which is developed through both "combative" and "parasitic" stances in relation to canonical authors. Overall, this study offers new information about modes of allusion in Jewish Greek literature and the relationship between the tracks of Homeric and Vergilian reception in cross-cultural contexts.